AACVD of Cu2−xS, In2S3 and CuInS2 thin films from [Cu(iBu2PS2)(PPh3)2] and [In(iBu2PS2)3] as single source precursors. (19th March 2015) - Malik, Sajid N.; Malik, Abdul Qadeer; Mehmood, Rana Farhat; Murtaza, Ghulam; Alghamdi, Yousef G.; Malik, Mohammad Azad
Abstract : Environmentally benign metal–organic precursors have been synthesized and used for the deposition of Cu2− x S, In2 S3 and CuInS2 thin films. Abstract : [In( i Bu2 PS2 )3 ] and [Cu( i Bu2 PS2 )(PPh3 )2 ] complexes have been synthesized and used as single source precursors to deposit thin films of cubic In2 S3 and Cu2− x S respectively on glass substrates by aerosol-assisted chemical vapor deposition (AACVD) at 350–500 °C. Thin films of CuInS2 have also been deposited by using 1 : 1 molar ratio of [In( i Bu2 PS2 )3 ] and [Cu( i Bu2 PS2 )(PPh3 )2 ]. The deposited thin films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray diffraction (EDX) techniques. Deposition of films at different temperatures showed significant variation in stoichiometry and microstructure. The CuInS2 thin films were ultrasonicated in toluene along with dodecanthiol for 3 hours to obtain a suspension of CuInS2 nanocrystallites with a diameter of ca. 18 ± 2 nm and a band gap of 1.59 eV.